A Russian Adaptation of the Emotional Contagion Scale - Kosonogov, Vladimir; Kuskova, Olga (Frontiers in Psychology, 2022)
The aim of the work was to develop and test the Russian version of the Emotional Contagion Scale. A sample of 518 volunteers from the general population filled in this questionnaire. We examined the 1-factor model (all the items), the 2-factor model (positive/negative) and the 5-factor model (love/happiness/fear/anger/sadness). To measure its construct validity, we asked different subsamples to complete questionnaires of empathy and sensation seeking. The coefficients of test-retest reliability, internal consistency and validity were acceptable. Only the 1-factor model showed acceptable properties by all psychometric criteria. We also observed the gender effect, that is women were more contagious, according to the total scale and all subscales.